Rare mosaic variant of GJA1 in a patient with a neurodevelopmental disorder - Rina Shimomura; Tomoe Yanagishita; Kumiko Ishiguro; Minobu Shichiji; Takatoshi Sato; Keiko Shimojima Yamamoto; Miho Nagata; Yasuki Ishihara; Yohei Miyashita; Keiko Ishigaki; Satoru Nagata; Yoshihiro Asano; et al. (Human Genome Variation)
Abstract GJA1 is the causative gene for oculodentodigital dysplasia (ODDD). A novel de novo GJA1 variant, NM 000165:c263C > T [p.P88L], was identified in a mosaic state in a patient with short stature, seizures, delayed myelination, mild hearing loss, and tooth enamel hypoplasia. Although the patient exhibited severe neurodevelopmental delay, other clinical features of ODDD, including limb anomalies, were mild. This may be due to differences in the mosaic ratios in different organs.